Real‐time monitoring and control of soluble signaling factors enables enhanced progenitor cell outputs from human cord blood stem cell cultures. Issue 6 (16th December 2013) - Csaszar, Elizabeth; Chen, Kun; Caldwell, Julia; Chan, Warren; Zandstra, Peter W.
ABSTRACT Monitoring and control of primary cell cultures is challenging as they are heterogenous and dynamically complex systems. Feedback signaling proteins produced from off‐target cell populations can accumulate, inhibiting the production of the desired cell populations. Although culture strategies have been developed to reduce feedback inhibition, they are typically optimized for a narrow range of process parameters and do not allow for a dynamically regulated response. Here we describe the development of a microbead‐based process control system for the monitoring and control of endogenously produced signaling factors. This system uses quantum dot barcoded microbeads to assay endogenously produced signaling proteins in the culture media, allowing for the dynamic manipulation of protein concentrations. This monitoring system was incorporated into a fed‐batch bioreactor to regulate the accumulation of TGF‐β1 in an umbilical cord blood cell expansion system. By maintaining the concentration of TGF‐β1 below an upper threshold throughout the culture, we demonstrate enhanced ex vivo expansion of hematopoietic progenitor cells at higher input cell densities and over longer culture periods. This study demonstrates the potential of a fully automated and integrated real‐time control strategy in stem cell culture systems, and provides a powerful strategy to achieve highly regulated and intensified in vitro cell manufacturing systems. Biotechnol. Bioeng. 2014;111: 1258–1264. © 2013 The Authors Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.